1991
DOI: 10.1159/000235397
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Substance P in the Allergic Reaction, Based on Two Different Provocation Models

Abstract: It was shown in two different provocation models (nasal and bronchial provocation) that substance P (SP) may play an important role in the neurogenic inflammatory response in upper and lower airway disease. (1) Pretreatment with SP augments the antigen challenge response of the nasal mucosa. (2) The baseline bronchoalveolar lavage (BAL) concentrations of SP are elevated 8-fold in allergies (pollen asthma) as compared with normals, even outside of season. (3) The SP concentration in BAL increases significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Recent studies have shown that local ap plication of SP enhances nasal secretion in humans [10] and also increases the nasal challenge response to antigen [ 11 ]. It is likely that VIP also plays an important role in allergic and nonallergic nasal disease, since VIP alters glandular secretion by augment ing the flow of electrolytes and fluid from salivary glands [12], In human nasal secre tion, VIP is present in small amounts (0-50 pmol/1) [ 13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that local ap plication of SP enhances nasal secretion in humans [10] and also increases the nasal challenge response to antigen [ 11 ]. It is likely that VIP also plays an important role in allergic and nonallergic nasal disease, since VIP alters glandular secretion by augment ing the flow of electrolytes and fluid from salivary glands [12], In human nasal secre tion, VIP is present in small amounts (0-50 pmol/1) [ 13].…”
Section: Introductionmentioning
confidence: 99%
“…may induce a release of tachykinin-like substances in tracheal preparations from sensitized guinea pigs. A finding of an increased amount of substance P in bronchoalveolar fluid after bronchial allergen challenge in humans [38] indicates a similar scenario in the airways of asthmatics.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, in the regulation of these mechanisms the neutral endopeptidase probably plays a key role. The recent finding of the increased amount of substance P in bronchoalveolar lavage fluid af ter bronchial allergen provocation in humans [35] is in fa vor of the similar scenario in the airways of asthmatics.…”
Section: Discussionmentioning
confidence: 92%